Implementasi Pancasila dalam Membangun Ekonomi Nasional yang Bebas dari Jeratan Imperialisme - Sabil Ryanzada; Falsya Fitriany; Devara Calista Putri; Galih Firmansyah Putra; Herli Antoni (Student Scientific Creativity Journal, 2025)
This research discusses the implementation of Pancasila values in building national economic independence that is free from neo-imperialism. Indonesia's economic dependence on foreign countries, which has increased in line with the global crisis, poses a challenge to foreign dominance in strategic sectors. This research aims to analyze how Pancasila values such as cooperation, social justice, and independence can be the basis for independent and equitable economic policies. The method used is library research with literature study and analysis of economic policy documents. The results show that the application of Pancasila values in the development of cooperatives and MSMEs as well as the distribution of economic resources can confront neo-imperialism and strengthen economic sovereignty. The research highlights the importance of synergy between the government, the private sector, and the community as well as policy reforms in favor of economic independence. In conclusion, the implementation of Pancasila values in economic policy can be a strong foundation for building sustainable national economic independence.